Advances in FRET‐based biosensors from donor‐acceptor design to applications - Wen‐Chao Yang; Shuang‐Yu Li; Shengnan Ni; Guozhen Liu (Aggregate, 2024)
Abstract Fluorogenic biosensors are essential tools widely used in biomedicine, chemical biology, environmental protection and food safety. Fluorescence resonance energy transfer (FRET) is a crucial technique for developing fluorogenic biosensors that provide mechanistic insight into bioprocesses through time‐spatial bioimaging in living cells and organisms. Although extensive FRET‐based sensors have been developed for detecting or imaging analytes of interest over the past decade, few comprehensive reviews have summarized the recent studies from the fundamental chemical angle about the design and application. In this work, the recent advance in the discovery of FRET biosensors using donor‐acceptor dye combinations is described and they are classified based on different types of analytes, such as mall molecules, proteins, enzymes, nucleic acids and metal ions. This review provides molecular‐level inspiration for the design of FRET‐based biosensors, aiding in their application in biosensing and bioimaging.